Yahoo Clever wird am 4. Mai 2021 (Eastern Time, Zeitzone US-Ostküste) eingestellt. Ab dem 20. April 2021 (Eastern Time) ist die Website von Yahoo Clever nur noch im reinen Lesemodus verfügbar. Andere Yahoo Produkte oder Dienste oder Ihr Yahoo Account sind von diesen Änderungen nicht betroffen. Auf dieser Hilfeseite finden Sie weitere Informationen zur Einstellung von Yahoo Clever und dazu, wie Sie Ihre Daten herunterladen.
Euler's Run, prove this?
An elastic track on the ground is of length 1, fixed at the start position, the other end pulled by a tractor so that the track stretches uniformly. At time = 0, a runner is at the start position, and begins running at constant speed v on the track. The tractor also begins pulling at constant speed v. Prove that when the runner reaches the tractor, the track is of length e, or Euler's number.
The runner is running on the track, which is being continually stretched. Relative to the elastic track, the runner runs at constant speed v. Relative to the ground, the tractor is moving at constant speed v. That is to say, the other end of the track is moving away from the fixed end at a constant speed v.
In other words, the length of the track is continually growing at a constant rate of v, that is:
L = 1 + v t
And the runner is on the elastic track.
If there was no elastic track, and both the runner and tractor proceed at constant speed v, the runner will never catch up with the tractor.
2 Antworten
- HosamLv 6vor 8 JahrenBeste Antwort
The runner is running with constant speed v with respect to the elastic track whose tip attached to the tractor is moving at a constant rate of v.
Therefore the absolute speed of the runner is the sum of its relative speed (with respect to the track) plus the speed of the point the runner has reached at time t.
i.e. dx/dt = v + v1
Now v1 / v = x / L , where L is the length of the total track at time t.
Thus v1 = v x / (v t + 1)
Thus dx/dt = v + v x / (v t + 1)
In standard form, the differential equation becomes
dx/dt - (v / (v t + 1) ) x = v
Using integrating factor of exp( integral (- v / (v t + 1) ) ) = exp ( - ln (vt + 1) ) = 1 / ( v t + 1)
we get d/dt ( (1/(vt+1) x ) = v (1/ (vt + 1)
Therefore integrating both sides, we get
x / ( v t + 1) = ln ( v t + 1)
i.e. x = (vt + 1) ln (v t + 1)
since L = vt + 1 , then when x = L we must have ln (vt + 1) = 1 that is (v t +1 ) = e
but ( v t + 1) = L, so L = e.
- Let'squestionLv 7vor 8 Jahren
I really do not understand teh question but would definitely like to read the answer so I am answering.